2020
DOI: 10.1111/age.12915
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the effects of the bovine POLLED variants

Abstract: Summary Horns are paired appendages on the head of bovine species, comprising an inner bony core and outer keratin sheath. The horn bud forms during early fetal development but ossification of the developing horn does not occur until approximately 1 month after birth. Little is known about the genetic pathways that lead to horn growth. Hornless, or polled, animals are found in all domestic bovids. Histological studies of bovine fetuses have shown that the horn bud does not form in polled individuals. There are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 75 publications
(155 reference statements)
2
17
0
Order By: Relevance
“…It suggested that the keratinization process at the horn bud may be necessary for the development of the calf’s horn after birth. This study did not find white protrusions or vacuolated keratinocytes in the EH horn bud tissue ( Figure 2 ), unlike WH horn bud tissue and this was consistent with the reported results [ 34 ]. Two terms related to keratinization were found among the top 20 results of Reactome enrichment analysis of the two groups of differentially expressed genes ( Figure 6 C), including keratin filaments bind cell-cell adhesion complexes (R-BTA-6809393) and keratinization (R-BTA-6805567).…”
Section: Discussionsupporting
confidence: 93%
“…It suggested that the keratinization process at the horn bud may be necessary for the development of the calf’s horn after birth. This study did not find white protrusions or vacuolated keratinocytes in the EH horn bud tissue ( Figure 2 ), unlike WH horn bud tissue and this was consistent with the reported results [ 34 ]. Two terms related to keratinization were found among the top 20 results of Reactome enrichment analysis of the two groups of differentially expressed genes ( Figure 6 C), including keratin filaments bind cell-cell adhesion complexes (R-BTA-6809393) and keratinization (R-BTA-6805567).…”
Section: Discussionsupporting
confidence: 93%
“…The two highest peaks in the PBS scan ( fig. 5 B ) cover IGF2BP2 , encoding an important protein in cell metabolism and development, and RXFP2 , a gene involved in horn development ( Li et al 2018 ; Aldersey et al 2020 ). Both also have elevated F ST values ( fig.…”
Section: Resultsmentioning
confidence: 99%
“…For the POLLED (hornless) trait, four genetic variants have been identified in an intergenic region of BTA1 (Aldersey et al . 2020). Another widespread and consequential gene variant is the PLAG1 Q allele, which led to the recovery of stature of cattle in the sixteenth to eighteenth centuries (Utsunomiya et al .…”
Section: Domestication Dispersal and Differentiation Of Breedsmentioning
confidence: 99%